2016
DOI: 10.1039/c6nj02642g
|View full text |Cite
|
Sign up to set email alerts
|

A novel nano-sized binuclear nickel(ii) Schiff base complex as a precursor for NiO nanoparticles: synthesis, characterization, DFT study and antibacterial activity

Abstract: We prepared a new nano-hexadentate Schiff base and its nickel(ii) complex using an ultrasonic method, which produced NiO with an average size of 53 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…The peak value at 3253 cm −1 was attributed to the ν(O–H) stretching band of HL 1 , whereas complexes 1 and 2 showed the expected absorption at 3263 and 3409 cm −1 , indicating the existence of O–H group from oxime. [ 45 ] Appearance of new weak bands in the far‐IR spectra of two complexes were assigned to ν(M–O) and ν(M–N) at 488, 454 cm −1 and 545, 540 cm −1 , respectively. The consequences were consistent with these obtained by X‐ray diffraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak value at 3253 cm −1 was attributed to the ν(O–H) stretching band of HL 1 , whereas complexes 1 and 2 showed the expected absorption at 3263 and 3409 cm −1 , indicating the existence of O–H group from oxime. [ 45 ] Appearance of new weak bands in the far‐IR spectra of two complexes were assigned to ν(M–O) and ν(M–N) at 488, 454 cm −1 and 545, 540 cm −1 , respectively. The consequences were consistent with these obtained by X‐ray diffraction.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the antibacterial activity may be attributed to the type and composition of the bacterial cell and membrane permeability, which is why the complexes show better activity against gram positive bacteria ( S. aureus ) than gram negative bacteria ( E. coli ). [ 65 ]…”
Section: Resultsmentioning
confidence: 99%
“…[NiSAP.Et2NH] and [NiSAP.pip] complexes. Numerous studies have been reported in the literature to prepare nanoparticles in this way [28][29][30][31][32][33][34][35][36][37][38][39]. The particle sizes of low soluble complexes were identified by Scanning Electron Microscope (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…41−43 There are only a few reported articles on the synthesis of nanoparticles using Schiff base complexes as precursors. 44,45 Herein, we report for the first time the synthesis and characterization of novel Co(II) Schiff base complexes.…”
Section: Introductionmentioning
confidence: 99%